Acquiring Bulk Anomalous Photovoltaic Effect in Single Crystals of a Lead‐Free Double Perovskite with Aromatic and Alkali Mixed‐Cations. Issue 16 (17th January 2023) - Hua, Lina; Tang, Liwei; Liu, Yi; Han, Shiguo; Xu, Haojie; Guo, Wuqian; Ma, Yu; Liu, Xitao; Luo, Junhua; Sun, Zhihua
Abstract: The bulk anomalous photovoltaic (BAPV) effect of acentric materials refers to a distinct concept from traditional semiconductor‐based devices, of which the above‐bandgap photovoltage hints at a promise for solar‐energy conversion. However, it is still a challenge to exploit new BAPV‐active systems due to the lacking of knowledge on the structural origin of this concept. BAPV effects in single crystals of a 2D lead‐free double perovskite, (BBA)2 CsAgBiBr7 (1, BBA = 4‐bromobenzylammonium ), tailored by mixing aromatic and alkali cations in the confined architecture to form electric polarization are acquired here. Strikingly, BAPV effects manifested by above‐bandgap photovoltage ( V OC ) show unique attributes of directional anisotropy and positive dependence on electrode spacing. The driving source stems from orientations of the polar aromatic spacer and Cs + ion drift, being different from the known built‐in asymmetry photovoltaic heterojunctions. As the first demonstration of the BAPV effect in the double perovskites, the results will enrich the family of environmentally green BAPV‐active candidates and further facilitate their new optoelectronic application. Abstract : For the first time, the bulk anomalous photovoltaic (BAPV) effect manifested by above‐bandgap photovoltage is demonstrated in lead‐free double perovskite crystals, (4‐bromobenzylamine)2 CsAgBiBr7 . The driving source of this BAPV effect stems from orientations of the polar aromatic spacer and Cs + ion drift.